Anterior Dens Screw Fixation for Traumatic C1-2 Lateral Subluxation With 3-Part Fractures of the C2 Axis (Dens, Lateral Mass, and Hangman Fractures): A Case Report. (9th December 2021) - Chang, Dong-Gune; Ko, Jong-Hyun; Park, Jong-Beom; Ju, Gang-Ik
Abstract : Introduction: To report the first case of traumatic C1-2 lateral subluxation with three-part fractures of the C2 axis (dens, lateral mass, and hangman fractures) that was successfully treated with only anterior dens screw fixation. Methods: A 56-year-old man was admitted to the hospital complaining of neck and left arm pains caused by a pedestrian traffic accident. Radiologic examination revealed traumatic C1-2 lateral subluxation, type 3 dens fracture (Anderson and D'Alonzo classification), fracture of both C2 lateral masses, and type 1 hangman fracture (Levine and Edwards classification). Results: Preoperative closed reduction of the C1-2 lateral subluxation was successfully achieved by skull traction using a Gardner-Wells tong. The patient underwent anterior dens screw fixation for type 3 dens fracture with posterior angulation. At the 2-year follow-up visit, good reduction of traumatic C1-2 lateral subluxation and solid fusion of all three-part fractures of the C2 axis were achieved with full range of motion and stability at the C1-2 joint. In addition, notable improvement of neck and left arm pains was achieved. Discussion: Preoperative closed reduction and anterior dens screw fixation can be considered as a less invasive and motion-preserving surgery for traumatic C1-2 lateral subluxation with three-part fractures of the C2 axis.